Molybdenum disulfide nanoparticles concurrently stimulated biomass and β-carotene accumulation in Dunaliella salina. (January 2021) - Luo, Shan-Wei; Alimujiang, Adili; Cui, Jianghu; Chen, Ting-Ting; Balamurugan, Srinivasan; Zheng, Jian-Wei; Wang, Xiang; Yang, Wei-Dong; Li, Hong-Ye
Highlights: Molybdenum sulfide nanoparticles (MoS2 NPs) is first tested in microalgae. MoS2 NPs stimulate cell growth and biomass of Dunaliella salina . MoS2 NPs combine with high light can enhance β-carotene production. A defined two stages cultivation also benefits the accumulation of neutral lipids. Abstract: Molybdenum disulfide nanoparticles (MoS2 NPs) hold tremendous properties in wide domain of applications. In this study, the impact of MoS2 NPs was investigated on algal physiological and metabolic properties and a two-stage strategy was acquired to enhance the commercial potential of Dunaliella salina . With 50 µg/L of MoS2 NPs exposure, cellular growth and biomass production were promoted by 1.47- and 1.33-fold than that in control, respectively. MoS2 NPs treated cells were subject to high light intensity for 7 days after 30 days of normal light cultivation, which showed that high light intensity gradually increased β -carotene content by 1.48-fold. Furthermore, analyses of primary metabolites showed that combinatorial approach significantly altered the biochemical composition of D. salina . Together, these findings demonstrated that MoS2 NPs at an optimum concentration combined with high light intensity could be a promising approach to concurrently enhance biomass and β -carotene production in microalgae.